Applications of q-Bessel-Struve Functions on Univalent Functions - Saddaf Noreen; Saiful R. Mondal; Muhey U. Din; Saima Mushtaq; Zhang Wei; Adil Murtaza (Mathematics)
In this paper, the authors derived some new sufficient conditions for q-close-to-convexity with respect to certain functions involving three different normalizations of q-Bessel–Struve functions. These new inequalities, under which the three normalizations of q-Bessel–Struve functions are q-close-to-convex associated with certain functions, hold for <semantics>v≥<mstyle scriptlevel="0" displaystyle="true">−32</mstyle></semantics> and for all <semantics>q∈<mfenced separators="" open="(" close=")">0,1</mfenced></semantics>. The work is new and has great importance because it shows the pivotal role between the q-special functions and geometric function theory.